Influence of weed management practices on growth parameters and seed yield of sunflower (Helianthus annuus L.): Influence of weed management practices on growth parameters and seed yield of sunflower (Helianthus annuus L.) - MADHUMATI S PUJERI; J A HOSMATH (Journal of Oilseeds Research, 2020)
Pre-emergence application of pendimethalin 38.7CS @ 750 g/ha followed by inter-cultivation recorded significantly higher growth parameters viz., plant height (202.5 cm), total dry matter production (170.4 g/plant), leaf area (144.6 dm2/plant), leaf area index (0.81) and seed yield (20.7 q/ha) of sunflower than all other treatments. This was on par with farmers’ practice. Net returns and benefit cost (B: C) ratio followed the similar trend.